Perbandingan Efektivitas Beberapa Pelarut Terhadap Kelarutan Cerumen Obturans Secara In Vitro - Syahrijuita, Syahrijuita; Pratiwi Rahardjo, Sutji; I. Djufri, Nani; Djamin, Riskiana (Lembaga Penelitian Universitas YARSI, 2011)
Cerumen obturans is a pahtological condition with no harmfull to the patients but can caused ear tumbness sensation, earache, hearing impairment, deafness and decreasing the quality of life.The objections of the study are to compare the effectivity of six solvents, that are aquadest, NaCl 0,9%, coconut oil, olive oil, carboglycerin 10% and sodium docusate 0,5% againts cerumen obturans by means of in vitro study and to know the most effective duration contact of a solvent to cerumen osmolarity. The study is a laboratory experimental by using 30 specimen of solid cerumen with weight of 40 mg for each. The cerumen osmolarity is established by Spectronic 21 spectrophotometer. The effectivity comparison of solvents are tested with One Way Anova with alfa 0,05.The effectivity of solvents have a significant differentiation especially inÃ‚Â 20th , 25th and 30th minutes. The spectrophotometer that used to established the osmolarity of cerumen have revelead a significant results only in aquadest and NaCl 0,9% againts coconut oil dan olive oil,Ã‚Â The effective duration of contact by in vitro study is Ã¢â€°Â¥ 20 minutes and tends to increased to 30 minutes. In 20th and 25th minutes, NaCl 0,9 % is the most effective solvent, while aquadest is most effective in 30th minutes. Olive oil and coconut oil are less effective solvents. Water-based solvents are more effective than lipid-based solvents.